Evaluation of the Implementation of the Principles of Law Enforcement, Transparency, and Accountability in the Implementation of Regional Head Elections During the Covid-19 Pandemic in the South Coast - Jeffry Micco Pratama; M Fachri Adnan (Program Pascasarjana Universitas Negeri Makassar, 2022)
The purpose of this study is to analyze the strengths and weaknesses of the application of the principles of the rule of law, transparency, and accountability in the implementation of the 2020 Pesisir Selatan Pilkada and to analyze the challenges and opportunities of applying the principle of the rule of law. law, transparency, and accountability in the implementation of the 2015 South Coastal Pilkada. 2020. D In supporting the implementation of the Pilkada with legal certainty, the Pesisir Selatan Regency KPU has determined 15 decisions, including: technical instructions for stages and programs; determination of voting day and date, technical instructions for nomination procedures; determination of nomination requirements, technical instructions for the implementation of socialization, technical instructions for working procedures for the Pesisir Selatan Regency KPU, standards and technical guidelines for preparing budget needs, goods and services needs, and honorariums; technical guidelines for the distribution and accountability of the budget; technical instructions for stages, programs and implementation schedules, technical instructions for the formation of PPK, PPS, and KPPS, technical instructions for updating voter lists, technical instructions for campaign implementation, technical instructions for the need and technical specifications for the prevention and handling of Covid-19 controlling protocol equipment in the implementation of elections. In addition, implementing health governance in collaboration with the Pesisir Selatan Regency Covid-19 Task Force Team. The political party that carries the pair of candidates and their campaign team, the Regency Bawaslu, and the Republic of Indonesia Police (POLRI) of the Pesisir Selatan Regency, known as the Pesisir Selatan Police.